A Macroporous Bioreactor Super Activated by the Recombinant Human Transforming Growth Factor-β3 - Ripamonti, Ugo; Teare, June; Ferretti, Carlo (Frontiers in Physiology, 2012)
Macroporous single-phase hydroxyapatite (HA) and biphasic HA/β-tricalcium phosphate with 33% post-sinter hydroxyapatite (HA/β-TCP) were combined with 25 or 125 µg recombinant human transforming growth factor-β3 (hTGF-β3) to engineer a super activated bioreactor implanted in orthotopic calvarial and heterotopic rectus abdominis muscle sites and harvested on day 30 and 90. Coral-derived calcium carbonate fully converted (100%) and partially converted to 5% and 13% hydroxyapatite/calcium carbonate (HA/CC) preloaded with 125 and 250 µg hTGF-β3, and 1:5 and 5:1 binary applications of hTGF-β3: hOP-1 by weight, were implanted in the rectus abdominis and harvested on day 20 and 30, respectively, to monitor spatial/temporal morphogenesis by high doses of hTGF-β3. Bone formation was assessed on decalcified paraffin-embedded sections by measuring the fractional volume of newly-formed bone. On day 30 and 90, single phase HA implants showed greater amounts of bone when compared to biphasic specimens; 5 % and 13 % HA/CC pre-loaded with 125 and 250 µg hTGF-β3 showed substantial induction of bone formation; 250 µg hTGF-β3 induced as yet unreported massive induction of bone formation as early as 20 days prominently outside the profile of the macroporous constructs. The induction of bone formation is controlled by the implanted ratio of the recombinant morphogens, i.e. the 1:5 hTGF-β3:hOP-1 ratio by weight was greater than the inverse ratio. The unprecedented tissue induction by single doses of 250 µg hTGF-β3 resulting in rapid bone morphogenesis of vast mineralized ossicles with multiple trabeculations surfaced by contiguous secreting osteoblasts is the novel molecular and morphological frontier for the induction of bone formation in clinical contexts.